Effect of water renewal on dominance hierarchy of juvenile Nile tilapia - Goncalves-de-Freitas, Eliane [UNESP]; Teresa, Fabricio Barreto [UNESP]; Gomes, Fernanda Sgarbosa; Giaquinto, Percilia Cardoso [UNESP] (Elsevier B.V., 2008)
Nile tilapia social position (Oreochromis niloticus) can be mediated by multiple channels, including chemical communication. Absence of chemical cues in the environment prevents hierarchical settlement among pairs, and enhances time spent in confrontations. The aim of this study was to test the effect of continuously renewed water flow on the establishment of hierarchical dominance in Nile tilapia juveniles. In this condition, a high frequency of attacks and disruption on hierarchical stability were expected because chemical cues for hierarchy maintenance could be washed out. After 3 days in isolation, the fish were paired by standard size but not by sex, and submitted to two conditions: continuously renewed water flow (RENEWED, n = 7) and non-renewed water flow (NONRENEWED n = 8). The paired fish were placed in an aquarium (40 cm x 30 cm x 40 cm) for 3 h; four 10-min sessions were video-recorded: the first, immediately after the fish were paired and the others 1, 2, and 3 h after pairing. Hierarchy was identified by a dominance index (DI = given attacks/received + given attacks) For each fish. The hierarchical stability was achieved by analyzing the difference between dominant DI and subordinate DI (DI-D). Hierarchy was established in both groups after second session because the DI was significantly higher for one fish of the pair. The frequency of attacks of the dominant fish in RENEWED and NONRENEWED conditions was similar in all observation sessions. The attack frequency by subordinate fish was also similar during the first three sessions (2-h pairing). However, the frequency of attacks by subordinate fish in the RENEWED condition was higher than in the NONRENEWED situation at the fourth observation session (means +/- S.E.: RENEWED = 2.83 +/- 0.94 x 10 min(-1) and NONRENEWED = 0.25 +/- 0.16 x 10 min(-1); Mann-Whitney, p = 0.04). At this point, a significant reduction of the DI-D was observed (means +/- S.E.: RENEWED = 0.70 +/- 0.11 and NONRENEWED = 1,00 +/- 0.002; Mann-Whitney, p = 0.04). The changes in DI-D were related to more frequent attacks by the subordinated fish in renewed water flow. According to our results, the unsteady agonistic interaction under renewed water flow leads to social instability. Thus, continuous water renewing can wash out relevant chemical substances and therefore disturb the dominance recognition by subordinate fish. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Chemical cues; social rank; communication; Cichlid; aggressiveness; hierarchical stability